Micro funds and its contribution to micro enterprises / Noorain Afif - Afif, Noorain (Faculty of Business and Management, 2011)
This study is obtaining to determine the contributions of micro funds to microenterprises. Feedback from people in micro enterprises on their experience in getting the micro financing for their micro enterprises will be use as a result for the study. The rising challenges in current economic had made the government to enhance the credit facilities to the SMEs including the micro enterprises. It is vital because of the micro enterprises had a huge potion in our economy and keep rising until now. Besides that, the mandate under the new Central Bank Act 2009 is strategically focused compare to Central Bank Act 1958 which the mandates are broadly defined in this research, we will focus more on the role of central bank in promoting sound, progressive and inclusive financial system. This refers to the establishment of microfinancing to small businesses that had allowed the small businesses in reaching for source of financing.